Cladribine and ocrelizumab induce differential miRNA profiles in peripheral blood mononucleated cells from relapsing–remitting multiple sclerosis patients - Arisi, Ivan; Malimpensa, Leonardo; Manzini, Valeria; Brandi, Rossella; Gosetti di Sturmeck, Tommaso; D’Amelio, Chiara; Crisafulli, Sebastiano; Ferrazzano, Gina; Belvisi, Daniele; Malerba, Francesca; Florio, Rita; Pascale, Esterina; et al. (Frontiers in Immunology, 2023)
Background and Objectives Multiple sclerosis (MS) is a chronic progressive neurological disease characterized by early-stage neuroinflammation, neurodegeneration and demyelination that involve a spectrum of heterogeneous clinical manifestations in terms of disease course and response to therapy. Even though several Disease Modifying Therapies (DMTs) are available to prevent MS-related brain damage; acting on the peripheral immune system with an indirect effect on MS-lesions. Individualizing therapy according to disease characteristics and prognostic factors is still an unmet need. Given that deregulated miRNAs have been proposed as diagnostic tools in neurodegenerative/neuro-inflammatory diseases such as MS, we aimed to explore miRNA profiles as potential classifiers of the relapsing-remitting MS (RRMS) patients’ prospects to gain a more effective DMT choice and achieve a preferential drug response. Methods Twenty-five adult patients with RRMS were enrolled in a cohort study, according to the latest McDonald criteria before (pre-Cladribine, pre-CLA; pre-Ocrelizumab, pre-OCRE, time T0) and after high efficacy DMTs, time T1, 6 months post-CLA (n=10, 7 F and 3 M, age 39.0 ± 7.5) or post-OCRE (n=15, 10F and 5M, age 40.5 ± 10.4) treatment. Age and sex matched fifteen healthy control subjects (9F and 6M, age 36.3±3.0) were also selected. By using Agilent microarrays, we analyzed miRNA profiles from peripheral blood mononuclear cells (PBMCs). MiRNA-target networks were obtained by miRTargetLink and Pearson’s correlation served to estimate the association between miRNAs and outcome clinical features. Results First, the miRNA profiles of pre-CLA or pre-OCRE RRMS patients compared to healthy controls identified modulated miRNA patterns (respectively 40 and 7 miRNAs). Direct comparison of the two pre-treatment groups at T0 and T1 revealed more pro-inflammatory patterns in the pre-CLA miRNA profiles. Moreover, both DMTs emerged as being capable of reverting some dysregulated miRNAs towards a protective phenotype. Both drug-dependent miRNA profiles and specific miRNAs, such as miR-199a-3p, miR-29b-3p and 151a-3p, emerged as potentially involved in these drug-induced mechanisms. This enabled the selection of miRNAs correlated to clinical features and the related miRNA-mRNA network. Discussion These data support the hypothesis of specific deregulated miRNAs as putative biomarkers in RRMS patients’ stratification and DMTs drug response.